2020
DOI: 10.3390/s20051295
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Resistive Optical NO Gas Sensor Devices Based on Cobalt Tetraphenylporphyrin Dispersed in Hydrophobic Polymer Matrix

Abstract: We report on an optical nitrogen oxide (NO) gas sensor device using cobalt tetraphenylporphyrin (CoTPP) dispersed in three kinds of hydrophobic polymer film matrix (polystyrene (PSt), ethylcellulose (EC), and polycyclohexyl methacrylate (PCHMA)) to improve humidity resistance. Our approach is very effective because it allows us to achieve not only high humidity resistance, but also a more than sixfold increase in sensitivity compared with CoTPP film due to the high dispersion of CoTPP in the polymer film. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Humidity is one of the most influential sources of interference in the development of chemical sensors [ 40 ] and no practical method has been demonstrated to solve it yet. From this perspective, the sensor system demonstrated in this study offers a potential and feasible application of chemical sensors to detect ammonia in human breath and in industrial samples as well as ammonia mixed with other amine gases at almost saturated humidity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Humidity is one of the most influential sources of interference in the development of chemical sensors [ 40 ] and no practical method has been demonstrated to solve it yet. From this perspective, the sensor system demonstrated in this study offers a potential and feasible application of chemical sensors to detect ammonia in human breath and in industrial samples as well as ammonia mixed with other amine gases at almost saturated humidity levels.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the sensitivity to moisture, researchers often use hydrophobic polymers, both for deposition on top of a sensitive film and for obtaining composite materials. Shiba et al [ 98 ] demonstrated how CoTPP dispersed in three hydrophobic polymer matrixes (polystyrene, ethylcellulose (EC) and polycyclohexyl methacrylate) affected the moisture resistance of the optical sensor to NO. The presence of a hydrophobic polymer matrix led not only to an increase in stability in a humid atmosphere, but also to an increase in sensitivity by more than six times due to the suppression of CoTPP aggregation.…”
Section: Sensing Layers For the Detection Of Gaseous Nomentioning
confidence: 99%
“… Typical responses of CoTPP film (black), CoTPP-EC film (red), CoTPP-PCHMA film (green) and CoTPP-PSt film to 10 ppm of NO/N 2 at 100 °C. The blue zone indicates the period of NO gas introduction [ 98 ]. …”
Section: Figurementioning
confidence: 99%
“…(B) 1 ppm of NO sensing at 100 °C under low humidity (<20 RH%) and high humidity (85 RH%) conditions for CoTPP-EC film (red solid line) and CoTPP film (black solid line). Reproduced with permission from ref . Copyright 2020 MDPI.…”
Section: Mitigation Of Humidity Interference In Colorimetric Sensing ...mentioning
confidence: 99%